Recent Advances in the Management of Neovascular Glaucoma. (22nd May 2013) - SooHoo, Jeffrey R.; Seibold, Leonard K.; Kahook, Malik Y.
ABSTRACT: The development of anti-vascular endothelial growth factor (VEGF) molecules has expanded the range of available treatment options for many ocular diseases, including neovascular glaucoma (NVG). A number of studies have explored the use of anti-VEGF agents as stand-alone or adjunctive treatment for NVG. Although no large, prospective, randomized trials have been performed to date, the growing body of knowledge suggests that anti-VEGF agents are effective at reversing iris and angle neovascularization and lowering intraocular pressure in patients with NVG. Response to a single injection is typically temporary; therefore, laser or incisional surgery is still necessary in most cases. Future research is needed to determine the optimal agent, dose, route of administration, and timing of treatment either as monotherapy or coupled with other medical and/or surgical interventions.